1991
DOI: 10.1213/00000539-199106000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Central Cholinergic Depression Reduces MAC for Isoflurane in Rats

Abstract: The role of central nervous system cholinergic neuromechanisms during inhalation (isoflurane) anesthesia was evaluated by measuring the minimum alveolar concentration (MAC) in rats before and after selective modulation of cholinergic neurotransmission in the brain. Cholinergic neurotransmission was depressed by reducing synaptic levels of acetylcholine with intracerebroventricular (ICV) injection of the selective anticholinergic hemicholinium-3 and with ICV injection of the presynaptic inhibitory autoreceptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Moreover, peripheral administration of nicotine is known to activate nociceptors (54,55) and several lines of evidence have shown that muscarinic agonists enhance antinociceptive effects, which are blocked by pretreatment with M 1 , M 2 , or M 3 muscarinic receptorantagonists (56). In contrast, inhibition of the muscarinic signaling pathway induced by reducing ACh levels, inhibiting ACh release, or administering scopolamine in rat brains decreases the minimum alveolar anesthetic concentration of inhaled anesthetics (57). Several anesthetics, such as isoflurane, depress M 1 -and M 3 -receptor function (13,58).…”
Section: Effect Of Tramadol On Voltage-dependent Ion Channelsmentioning
confidence: 99%
“…Moreover, peripheral administration of nicotine is known to activate nociceptors (54,55) and several lines of evidence have shown that muscarinic agonists enhance antinociceptive effects, which are blocked by pretreatment with M 1 , M 2 , or M 3 muscarinic receptorantagonists (56). In contrast, inhibition of the muscarinic signaling pathway induced by reducing ACh levels, inhibiting ACh release, or administering scopolamine in rat brains decreases the minimum alveolar anesthetic concentration of inhaled anesthetics (57). Several anesthetics, such as isoflurane, depress M 1 -and M 3 -receptor function (13,58).…”
Section: Effect Of Tramadol On Voltage-dependent Ion Channelsmentioning
confidence: 99%
“…Moreover, three cross-sectional population-based studies have demonstrated that anticholinergic drug intake is an important factor in determining the severity of cognitive impairment [15], [16], [17]. Because previous studies have shown that volatile anesthetics have anticholinergic properties [18], we hypothesized that pretreatment with the acetylcholinesterase inhibitor donepezil, which has been approved by the Food and Drug Administration (FDA) for the treatment of Alzheimer's disease, may prevent isoflurane-induced spatial memory impairment in aged mice.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that the release, presence, and activity of acetylcholine within the cerebral cortex, pontine reticular formation, and striatum are suppressed during general anesthesia 4548 . Decreased cholinergic transmission lowers the minimum alveolar concentration for isoflurane in the rat 49 , while enhanced cholinergic tone in the brain can reverse isoflurane anesthesia 10 . Systemic or cortical application of atropine prevents NBM-mediated electroencephalogram desynchronization 50,51 .…”
Section: Discussionmentioning
confidence: 99%